Delusions of grandeur? Aria and the development of Soviet metal music - Hazle, Dawn (2018)
During the early 1980s in Soviet Russia, culture was regulated in order to control the population's exposure to potentially ideologically problematic themes and ideas. This meant that much Western music was not available in officially sanctioned formats including records, radio broadcasts and concerts, and so Western music entered the USSR via physical copies of records brought in by travellers returning from abroad. The unofficial culture that centred on rock music in the Soviet Union shares some features with the development of metal music in different global contexts. Metal music tended to spread from its 1960s Birmingham origins in the same stages as those that occurred when rock entered Soviet Russia: local performers first copied the songs they heard on imported records and then began to translate these songs into the local language from English; finally, original songs were composed in the local language. Soviet Russian metal music can be considered more of a part of the rock scene compared to metal in Western cultures, because it followed the same routes. This closer relationship is also evident in the relationship between rock, metal and authenticity in Soviet Russian culture, since Russian rock’s underground nature meant it retained a closer tie with authenticity than its Western counterpart. Authenticity can be compared to Yurchak’s concept of 'vnye', the idea that non-Soviet is not the same as anti-Soviet, and this thesis proposes the idea that 'vnye' can be used to replace the anti-commercial-based authenticity of Western metal which is practically irrelevant in socialist societies.